65.0k views
5 votes
Use the quadratic formula to solve the equation. If necessary, round to the nearest hundredth. −6y^2 − 9y = −1

A, –9.5, 8


B, –0.1, 1.6


C, –3.21, 0.21


D, –1.6, 0.1

User Alex Yu
by
6.7k points

2 Answers

1 vote

Answer:

D, -1.6, 0.1

Explanation:

I made a 100% on my posttest and this was one of the qustions. Trust.

User Abhishek Kanojia
by
6.6k points
3 votes
It is usually nicer to work with positive numbers, so add the opposite of the left side of the equation.
0 = 6y² + 9y -1
You identify a=6, b=9, c=-1 for the quadratic formula, which tells you
y = (-b ±√(b²-4ac))/(2a)
y = (-9 ±√(9²-4(6)(-1)))/(2·6)
y = (-9 ±√105)/12
y = -1.60, 0.10

The appropriate choice is
D, -1.6, 0.1

_____
You don't really need to solve the equation if you can test the offered solutions. Dividing by the coefficient of y², your equation becomes
y² + (3/2)y - (1/6) = 0
This tells you the sum of the roots will be -3/2 (the opposite of the y coefficient), and their product will be -1/6 (the constant term). Selections A and C have the wrong product; selection B has the wrong sum.
Use the quadratic formula to solve the equation. If necessary, round to the nearest-example-1
User Peadar Doyle
by
5.2k points